2014
DOI: 10.1002/2013gc005113
|View full text |Cite
|
Sign up to set email alerts
|

A 249 kyr stack of eight loess grain size records from northern China documenting millennial‐scale climate variability

Abstract: In order to construct a stacked climatic record of millennial-scale variability for northern China, grain size was measured for 12,330 samples from eight thick loess sections. Between section correlation of these grain size records shows that, although small depositional hiatuses may be present within a single section, most parts of the sections display continuous dust deposition. By correlating the eight records with the precisely dated Chinese stalagmite d 18 O record, a stacked 249 kyr-long grain size time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
88
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 109 publications
6
88
1
Order By: Relevance
“…The radiocarbon ages of S 0 and L 1-1 overlap with or are slightly younger than the dates of HTM (∼11-5 ka) and LGM (∼26.5-19 ka), respectively. Because measured 14 C ages of soil organic matter are always younger than the true age of deposition, due to addition of younger organic matter through rootlet penetration, bioturbation, and percolation of soluble organic substances (32,35), our radiocarbon dates are compatible with the widely accepted assumption that the coarsest interval of L 1-1 represents the coldest interval of the LGM, whereas the finest interval of S 0 represents the warmest interval in the Holocene (22,24). At each site, the samples dated were selected from the finest-grained part of the Holocene soil (S 0 ) and the coarsest part of the LGM loess unit (L 1-1 ).…”
Section: Significancesupporting
confidence: 74%
See 2 more Smart Citations
“…The radiocarbon ages of S 0 and L 1-1 overlap with or are slightly younger than the dates of HTM (∼11-5 ka) and LGM (∼26.5-19 ka), respectively. Because measured 14 C ages of soil organic matter are always younger than the true age of deposition, due to addition of younger organic matter through rootlet penetration, bioturbation, and percolation of soluble organic substances (32,35), our radiocarbon dates are compatible with the widely accepted assumption that the coarsest interval of L 1-1 represents the coldest interval of the LGM, whereas the finest interval of S 0 represents the warmest interval in the Holocene (22,24). At each site, the samples dated were selected from the finest-grained part of the Holocene soil (S 0 ) and the coarsest part of the LGM loess unit (L 1-1 ).…”
Section: Significancesupporting
confidence: 74%
“…These results strongly support the idea that the Earth's thermal equator will move northward in a warmer world, and that the observed southward migration of the monsoon rain belt over the last few decades is transient and northern China will eventually become wet as global warming advances. studies (19,20,22,25) demonstrate that (i) L 1-1 was deposited in marine isotope stage (MIS) 2 (∼27-11 ka), which includes the LGM (∼26.5-19 ka) (26); (ii) S 0 was deposited in the early-midHolocene (∼11-3 ka), which includes the Holocene Thermal Maximum (HTM) (∼11-5 ka) (27); and (iii) L 1-2 was deposited in late MIS 3 (∼38-27 ka). To ensure that we used a complete cold-warm cycle for C 3 /C 4 vegetation reconstruction, almost all of the sections were sampled down to loess unit L 1-2 .…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have speculated that millennial-scale oscillations represent a teleconnection between the North Atlantic and East Asia (e.g., Porter and An, 1995;Yang and Ding, 2014), although the dynamics involved are poorly understood. Porter and An (1995) and Sun et al (2012) suggested, based on CLP loess physical characteristics, that a strong influence from the westerlies resulted in transport of the North Atlantic signal to East Asia.…”
mentioning
confidence: 99%
“…Porter and An (1995) and Sun et al (2012) suggested, based on CLP loess physical characteristics, that a strong influence from the westerlies resulted in transport of the North Atlantic signal to East Asia. Conversely, Yang and Ding (2014) proposed that millennial-scale North Atlantic climate signals might have been transmitted to the Siberian High via the Barents and Kara Sea ice sheets, and were propagated eastwards to the CLP via the winter monsoon system. In the western CLP (Chen et al, 1997), for example, evidence of millennial-scale (likely Heinrich) events are preserved within the loess stratigraphy during phases of strong winter monsoon in China; however, not all of the strong winter monsoon events in China correlate with Heinrich events in the North Atlantic, so challenging the Yang and Ding (2014) hypothesis.…”
mentioning
confidence: 99%